2021
DOI: 10.4018/ijsecsr.2021070102
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurship Competence and SME Sustainability in Kampala, Uganda

Abstract: This study was carried out to establish the possibility of enhancing SME sustainability in Kampala, Uganda through boosting key internal drivers of entity performance (records management, internal communication, family influences, and online presence). Using conclusive, cross-sectional, and case study research designs supported by the philosophical underpinnings of critical realism and positivism epistemology, data was collected from 278 SMEs using semi-structured questionnaires. Using SEM analysis, it was rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Bensalah and Tinaztepe (2021) stated that most Moroccan entrepreneurs that become successful are educated and utilize their education to improve their ventures' performance for success. Another quantitative study found a higher education level of owners/managers is one of the drivers that are key to the sustainability of their ventures (Rulangaranga, D. M., & Isoh, A. V. N., 2021). Therefore, Rulangaranga and Isoh argued that entrepreneurs must consider educated managers to enhance the sustainability of their SMEs.…”
Section: Education Levelmentioning
confidence: 99%
“…Bensalah and Tinaztepe (2021) stated that most Moroccan entrepreneurs that become successful are educated and utilize their education to improve their ventures' performance for success. Another quantitative study found a higher education level of owners/managers is one of the drivers that are key to the sustainability of their ventures (Rulangaranga, D. M., & Isoh, A. V. N., 2021). Therefore, Rulangaranga and Isoh argued that entrepreneurs must consider educated managers to enhance the sustainability of their SMEs.…”
Section: Education Levelmentioning
confidence: 99%